Common bile duct stone development due to a Hem-o-lok clip migration: a rare complication of laparoscopic cholecystectomy - Roh, Yong Jun (BMJ Case Rep, 2019)
Surgical clip migration is a rare complication of laparoscopic cholecystectomy (LC). Surgical clips migrating into the common bile duct (CBD) can lead to stone formation and obstruction. Here, we report a case of acute cholangitis caused by surgical Hem-o-lok clip migration into the bile duct with stone formation 13 months after LC. A 65-year-old man who underwent LC presented with upper abdominal pain and fever for 3 days. Abdominal CT scan showed a radiopaque material in the CBD, diffuse wall thickening and dilatation of intrahepatic and extrahepatic duct. Emergency percutaneous transhepatic biliary drainage was performed. Twodays later, an endoscopic retrograde cholangio-pancreatography was implemented, and muddy stones and one surgical clip were successfully removed by extraction balloon catheter.